UHPLC-(+)APCI-MS/MS determination of oxygenated and nitrated polycyclic aromatic hydrocarbons in airborne particulate matter and tree barks collected in Buenos Aires city - Fujiwara, Fabián Guillermo (2014)
A study was undertaken to evaluate the content of oxygenated and nitrated polycyclic aromatic hydrocarbons (OPAHs and NPAHs) in airborne particulate matter (PM2.5 and PM10), and tree barks. For PM2.5 and PM10 collection different approaches were followed using different type of filters and sample collectors. Samples of PM2.5 were collected on glass fiber filters during one month with a medium volume sampler. For PM10, glass and quartz fiber filters were used and samples were collected simultaneously for one week using a high volume sampler. In addition, bark samples were collected at the same sites. Ultra high performance liquid chromatography-atmospheric pressure chemical ionization tandem mass spectrometry (UHPLC-APCI-MS/MS) was used for PAHs derivatives quantification. Data acquisition under MS/MS was achieved by applying multiple reaction monitoring to provide a high degree of sensitivity and specificity. Chromatographic separation was performed on a reverse phase rapid resolution column using a gradient mode (total run time: 5.0 min). The study evidenced that in airborne particles matter, four PAHs derivatives were detected at concentrations from 0.01 to 240.62 ng m-3 (or 0.3 µg g-1 to 30 mg g-1). Meanwhile, in tree barks, only OPAHs were detected at concentrations varying from 0.18 to 0.72 µg g-1.